46 Impact of early versus late medical treatment of a hemodynamically significant patent ductus arteriosus on time to reach full feeds in preterm neonates. (29th October 2021) - Yadav, Krishan; Ting, Joseph; Castaldo, Michael; Grewal, Gurpreet; Kuan, Mimi
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Prolonged exposure to a hemodynamically significant patent ductus arteriosus (hsPDA) in preterm infants has been associated with an increase in neonatal morbidities. Objectives: To examine the effect of timing of medical treatment (within first 7 days of life versus after 7 days of life) for a hsPDA on the duration to achieve full feeds in infants born at <30 weeks of gestation. Design/Methods: This was a retrospective cohort study in a quaternary neonatal intensive care unit (NICU) with a targeted neonatal echocardiography service. Infants admitted between July 2015 – June 2019 who received medical treatment for an hsPDA were included and grouped based on those who received first medical therapy within 7 days of life (early treatment) and after 7 days of life (late treatment). An hsPDA was defined using both clinical (worsening ventilation, pulmonary hemorrhage/edema, or hypotension requiring inotrope or hydrocortisone) and echocardiographic findings (LA/Ao ratio >1.4; LVO >350 mL/kg/min, PDA >1.4 mm, IVRT < 35 ms). Duration to reach full feeds was calculated based on number of days to reach a total enteral feed ≥ 120 mL/kg/day with no parenteral source of nutrition. Results: Forty-six infants met the inclusion criteria. Of the 46 infants, 24 were identified as receiving early treatment and 22 received late treatment. Infants in the early treatment group had lower median birth weight than the late treatment group (802 g vs. 1016 g, p=0.022). All other clinical characteristics were not significantly different. No significant difference was found in the use of indomethacin, ibuprofen, or acetaminophen as the initial medical treatment (Table 1). The late treatment group had elevated left ventricular output (median: 286 vs. 369 mL/kg/min, p=0.013) and tricuspid annular plane systolic excursion (median: 6 vs. 8 mm, p=0.002) (Table 2). Infants in the early treatment group reached full feeds earlier than those in the late treatment group (19 vs. 30 days, p=0.042) (Table 1). Conclusion: Early medical treatment of hsPDA was associated with shorter duration to reach full feeds in our cohort of preterm infants. Further larger scale study is needed to understand the association between the timing of medical therapy and prolonged exposure of splanchnic circulation to hemodynamically significant ductus.